Educational management and technical efficiency with official secondary schools in Florencia, Caquetá, Colombia - Pardo-Rozo, Yelly Yamparli; Cabrera-Gasca, Leonel; Pinzón-Hermosa , Luis Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The objective of the study is to measure the technical efficiency in secondary education institutions (IEM), in Florencia, Colombia, and to identify actions to strengthen educational management from the perspective of the rectors. The research is of a mixed type and the technical efficiency indicator was determined in a sample of 18 IEM, based on the analysis of the data envelope. An interview was conducted with the Directors of the IEMs and a DOFA (Weaknesses, Opportunities, Strengths, Threats) matrix was constructed. The results indicate that 39% of the IEM are efficient and 61% have potential for improvement in the use of classroom capacity and teaching work. Awareness activities are proposed for the academic community and parents, on the importance of the educational process and results of the Saber tests and the fulfillment of the resources for the School Feeding Programs and transportation service.